Relation between cooperation and organizational learning with the competitiveness in an interorganizational network - Zonta, Paulo Cesar (2015)
The study analyzed the relationship between cooperation and organizational learning with competitiveness in a small and medium enterprises (SME) network, with business of the groups of the Commercial and Industrial Association of Chapecó (ACIC). The methodology used was quantitative, with the factorial analysis. Currently, ACIC has 14 groups and 236 SME´s nucleated, developing joint activities of economic and social sustainability in Chapecó. The theoretical study raised concepts already endorsed by the scientific community on interorganizational networks, competitiveness, cooperation and organizational learning. The results demonstrated that indicators related to cooperation and learning in horizontal networks are characterized as antecedents of competitiveness in organizational networks, and that there is a positive correlation between the constructs cooperation and organizational learning with competitiveness construct. The study confirms the belief that small businesses associated in networks can increase their competitiveness, thus contributing to regional development.